Performance evaluation of a modified LED motorcycle headlamp with an acrylic optical limiting plate - Dwi Prasetyo; Beni Setya Nugraha; Ayu Sandra Dewi; Ruolan Li; Dangshe Qiu (Universitas Negeri Yogyakarta, 2026)
Nighttime riding safety depends strongly on headlamp performance, especially for motorcycles operating in road environments with limited street lighting. Conventional halogen lamps are widely used but place a relatively high electrical demand and thermal load on the system. This study experimentally evaluates a modified 12 W light-emitting diode (LED) motorcycle headlamp equipped with a 3 mm acrylic optical limiting plate to improve beam control and reduce upward light scatter. A Honda Supra 125 FI with a 12 V direct-current electrical system was used as the test platform. The final quantitative comparison was limited to a standard 35 W halogen lamp and a modified LED configuration with an acrylic shield/baffle. Luminous intensity was measured at 1 m and 5 m, electrical current was measured under direct-current operating conditions, and surface temperature was monitored during a 75 min continuous operation test. The modified LED system produced 1342 lux at 1 m and 170 lux at 5 m, exceeding the halogen values of 1240 lux and 124 lux, respectively. The LED configuration reduced current draw from 2.92 A to 1.00 A and decreased peak operating temperature from 278 °C to 100 °C. The acrylic limiting plate produced a more clearly bounded beam pattern in qualitative projection tests; however, the present study does not claim full glare elimination because standard glare indices and complete photometric mapping were not measured. These results indicate that the proposed LED retrofit can improve energy efficiency and thermal behavior while providing better preliminary beam control for motorcycle lighting applications.